PERAN PGRI DALAM PELANGGARAN KODE ETIK GURU, BERDAMPAK PADA TUJUAN PEMBELAJARAN - Agustrio Mahanggana Angkat; Anggelina Labora Dorasi Lumban Gaol; Ayub Desrika Simorangkir; Juwita Helena Sitompul; Philip Hamonangan Sinaga; Rohana Manalu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The teacher's code of ethics is a guideline for teachers' behavior in maintaining the integrity and professionalism of teachers in the world of education. Violations of the teacher's code of ethics such as discrimination, abuse of authority or power and extortion can affect the effectiveness of the implementation of the teacher's code of ethics which has an impact not only on the teacher but also on students and parents of students. The existence of PGRI certainly plays a role in supporting a conducive classroom atmosphere through the implementation of an effective teacher's code of ethics. PGRI (Indonesian Teachers Association) has a significant role through policy advocacy training and competency development. With the implementation of a good code of ethics, it is hoped that students will be created who are moral and responsible. This study uses qualitative descriptive through interviews and literature studies with the results showing that violations of the teacher's code of ethics have a negative impact on the achievement of learning objectives and student quality.